Significance of IOT- Oriented Marketing Management for Consumer Products: The Integration of IoT in Marketing Management for Enhanced Consumer Engagement (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Internet of Things (IoT) is predicted to be one of the primary raising megatrends in technology. Mixed with present and expected pervasiveness and ubiquity of connected consumer products it provides ground to program in a number of places, including marketing. IoT is going to influence the decision-making approach in different phases of selling, buying as well as the marketing process. Thus, every person as well as a business ought to know precisely what IoT is actually, and why and how they need to integrate it in their operations. growing number of freshly released products have been in a position to sense the planet of theirs as well as share data with owners, various other products, companies or and through the web of Things (IoT). This motivated us to suggest an intelligent method based on IoT to assist businesses marketers make an effective marketing program via using obtained data from IoT devices. With pragmatic examples and theoretical framework, the newspaper gives related concepts as well as managerial implications of IoT in retail and marketing.